The impact of information and communications technology on political behavior - Salih, Dana Ali (Journal of Legal and Political Studies, 2014)
This research analyzes a very important topic, which is (The Impact of Information and Communication Technologies in Political Behavior). It is important since the world nowadays is witnessing great and rapid development in the field of information and communication technology. Moreover, the world has become more like a small village interconnected. One of the most outstanding things occurred as a result of the impact of this technology is the political behavior of individuals in modern societies . The repercussions of the leading information and communications technology in political behavior have emerged in the increasing of political awareness of citizens and the spread of political culture and strengthening. This has reflected effects in motivating and energizing political participation and to find more effective and stronger ways for the exercise by the citizens as well as to give a big boost toward accelerating events and public reaction about the issues that concern them, humanitarian issues, speeding up the transfer of cultures, experiences of struggle and interaction between peoples . The information and communication technologies play an increasing role in political socialization in a way that states may not be content with it, where as a result of the vast amount of information exchanged between cultures and peoples and their institutions, distances as well as the geographic and political boundaries have been cancelled. Thus, individual political behavior has been influenced by information and communication technology as this technology has generated many ways of doing Politics by individuals which did not exist before, and also expanded ways to exercise it in simpler, stronger and more effective ways.
Keywords: Information Technology; Communication Technologies; Political Behavior; Technology; Politics